استخدام فيديو تيك توك لترقية مهارة الاستماع والكتابة لطلاب الفصل الخامس بالمدرسة الإبتيدائية الصلاح كجران كوندانج ويتان باسوروان - مفيدة, نور; رحلة الشتاء, ولدا (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
Arabic language teaching is based on four skills: listening, speaking, reading and writing. Learning to write and listen requires special attention because they are difficult skills. The using of Tiktok application program, can be a good media for teaching listening skills because many students are confused and difficult to rewrite vocabulary. Therefore researchers use Tik Tok videos to teach skills listening and writing. The purpose of this study is to measure the effectiveness of learning Arabic language by using Tik Tok application. This research is a quantitative research by using experimental research, in one group. All students of grade V of SD Assholach were sampled with 18 students. Researchers analyzed the quantitative environment of student test results in the statistics program, to measure the effectiveness of using Tik Tok videos to improve listening and writing skills of grade V students of Assholach Elementary School . The author uses pretest and post test using t-test to measure the effectiveness of this  method in Arabic language teaching. The results of this study: 1) The steps for using Tik Tok videos to improve listening and writing skills are as follows: (a) researchers prepare Tik Tok video clips; (b) researchers show Tik Tok videos using LCD; (c) Provide exercises in the form of questions or mention vocabulary or with beautifulnan to test the improvement of their listening and writing skills using Tik Tok videos. 2) from the results of students from the pre test and post test in  one group using the spss test - the average in the Pre-test test is 47.5, and the post-test is 80, turns out that the use of Tik Tok videos is effective for improving Listening and writing skills. يقام تعليم اللغة العربية على أربع مهارات وهي مهارة الإستماع والكلام والقراءة والكتابة. وتعلم الكتابة والإستماع تحتاج إلى اهتمام خاص لأنهما من مهارة صعبة. وكل المهارات تحتاج إلى الوسائل التعليمية، ووسائل الجيدة هي وسيلة يمكن استخدامها لأي مواد وتطورت بشكل مستمر مع الزمن وأحدها بتطبيق برنامج تيك توك لأن بعد ملاحظة إلى المدرسة وجدت الباحثة بأن أداة تدريس لمهارة الإستماع هي بصوة المدرس فقط وكثيرمن الطلاب متحيرة وصعوبة في إعادة كتابة المفردات التي حفظواها فلذالك أخذت الباحثة باستخدام فيديو تيك توك في تعليم مهارة الإستماع والكتابة. وأهداف هذا البحث هي لوصف خطوات استخدام فيديو تيك توك ولمعرفة فعالية استخدام فيديو تيك توك لترقية مهارة الإستماع و الكتابة لطلاب فصل الخامس بالمدرسة الإبتيدائية الصلاح كجران. هذا البحث هو البحث الكمي. وتسمى ببحث التجريبي، في المجموعة الواحدة. وعينبة هذا البحث جميع الطلاب في فصل الخامس بمدرسة الإبتدائية الصلاح عددهم 18 طلابا. حللت الباحثة البيانات الكمية من نتائج الإختبار الطلاب ببرنامج الإحصاء. تعتمد الباحثة على نتيجة الإختبار القبلي والإختبار البعدي باستخدام اختبار "ت" (t-test) لقياس فعالية هذه الوسيلة في تعليم اللغة العربية.  وأما نتائج هذا البحث: 1) أن خطوات استخدام فيديو تيك توك لترقية مهارة الإستماع والكتابة كما يلي:(أ) قامت الباحثة باستعداد مقاطع فيديو تيك توك، (ب) عرضت الباحثة فيديو تيك توك على شاشاة الكريستال السائل، (ج) إعطاء تمرينات على شكل الأسئلة أو ذكر المفردات أو باللعب لإختبار تحسينهم في مهارة الإستماع والكتابة باستخدام فيديو تيك توك. 2) بالنظر إلى نتيجة الطلاب من اختبار القبلي والبعدي في مجموعة الواحدة باستخدام spss بإختبار "ت" .t- test أن معدل في اختبار القبلي هي 47,5 وأما اختبار البعدي هي 80 ونسبتها 32,5 فحصل أن استخدام فيديو تيك توك فعال لترقية مهارة الإستماع والكتابة.